Maternal nutrition during pregnancy and its association with birth outcomes and neonatal body composition in the context of HIV in urban Black South Africans - Wrottesley, Stephanie Victoria (My University, 2018)
Background: Maternal pre-pregnancy overweight and obesity and excessive gestational weight gain (GWG) are established predictors of fetal growth, which substantially increase the risk of adverse birth outcomes, such as high birth weight and large-for-gestational age deliveries. While sub-optimal growth in utero has serious implications for infant health in the short term, nutritional insults during this critical period of plasticity may additionally impair growth and development of body tissues and thereby, increase long-term risk of obesity and non-communicable diseases in later life. This double burden of malnutrition (maternal overweight coupled with micronutrient deficiencies) is of particular relevance to low-or middle-income countries, such as South Africa, where rapid urbanisation and a transition towards diets high in saturated fat, sugar, salt and processed foods and decreased levels of physical activity has resulted in substantial increases in obesity. Although the implications of anthropometrically defined maternal nutritional status (MNS) on birth size have been well established, the role of dietary patterns within these relationships has not been thoroughly examined. In addition, the use of birth weight as a proxy for fetal growth does not distinguish between the components of body composition (i.e. fat mass and fat-free mass), which may be more indicative of metabolic risk. Lastly, the influence of other maternal factors such as human immunodeficiency virus (HIV) on the associations between maternal nutrition and infant outcomes and metabolic risk is yet to be explored. Aim: The overall aim of this thesis was to examine maternal nutrition (nutritional status; dietary patterns) of urban, black South African women and explore the relationship between maternal dietary patterns during pregnancy and birth outcomes (including neonatal body composition). Furthermore, the extent to which other maternal factors – i.e. HIV/antiretroviral treatment (ART) status, body mass index (BMI) at recruitment, GWG, demographics, socioeconomic status etc. - act as confounders or effect modifiers to these associations was explored. The following four specific study components addressed this aim: 1) To review and report on MNS in African women and its associations with fetal, birth, neonatal and infant outcomes in the first 1000 days; 2) to compare body composition measurements using two methods, namely (i) dual-energy x-ray absorptiometry (DXA) and (ii) air displacement plethysmography (ADP; Peapod), in black South African neonates; 3) to characterise, depict and report on maternal dietary patterns during pregnancy using multivariate dimension-reduction techniques in urban black South African women and to examine the association between dietary patterns and GWG in the context of other maternal lifestyle and socioeconomic factors; and 4) to examine the associations between maternal dietary patterns and birth size and neonatal body composition and explore how specific maternal factors – i.e. HIV/ART status, maternal BMI and GWG – may influence these associations. Methods: Comprehensive literature searches were independently performed by two researchers in May 2015 in order to identify all relevant studies conducted in Africa. The review used a systematic approach to search the following databases: Medline, EMBASE, Web of Science, Google Scholar, ScienceDirect, SciSearch and Cochrane Library. Full-text articles were obtained and reviewed and data were extracted from relevant publications into tables appropriately. Within a wider longitudinal cohort study taking place in Soweto, Johannesburg (the Soweto First 1000-Day Study; S1000), habitual dietary intake of 538 pregnant women was assessed using a quantitative food-frequency questionnaire and dietary patterns were depicted via principal component analysis. Associations between dietary patterns and BMI-specific GWG were analysed using linear and multinomial logistic regression. ―Traditional‖ diet pattern adherence (pattern score) was used to classify maternal diet for the final study objective (objective 4) and multiple linear regression models were used to examine associations between maternal ―traditional‖ diet pattern score, HIV/treatment status [three groups: HIV negative, HIV positive (antenatal ART initiation), HIV positive (pre-pregnancy ART initiation)], BMI and GWG (kg/week) and: newborn (1) weight-to-length ratio (WLR, kg/m) in 393 mother-neonate pairs; (2) Peapod estimated fat mass index (FMI, kg/m3) in a 171-pair subsample. Results: Twenty-six studies met the inclusion criteria for the literature review (objective 1). Overall, MNS in Africa showed features typical of the epidemiological transition; including higher overweight and obesity and lower underweight prevalences, alongside high anaemia prevalences’ and poor-quality diets. Maternal BMI and GWG were positively associated with birth weight; however, maternal overweight and obesity were associated with both increased macrosomia (birth weight >4kgs) and intrauterine growth restriction risk. In addition, maternal anaemia was associated with lower birth weight and both macro- and micronutrient supplementation during pregnancy was associated with improvements in GWG, birth weight and mortality risk. During the comparison of body composition assessment techniques (objective 2), significant correlations were observed between ADP and DXA measurements of fat mass (r = 0.766; p<0.001), fat-free mass (r = 0.942; p<0.001) and %fat (r = 0.630; p<0.001). However, fat mass (408 ± 172 g vs. 337 ± 165 g; p<0.001) and body fat percentage (12.9 ± 4.4% vs. 9.9 ± 4%; p<0.001) were significantly higher and fat-free mass (2681 ± 348 g vs. 2969 ± 375 g; p<0.001) significantly lower when estimated by ADP than by DXA. There was greater consistency in the estimation of fat-free mass between the methods when compared to estimates of fat mass and body fat percentage. Longitudinal assessment (objectives 3 and 4) identified three dietary patterns in urban black South African women during pregnancy: namely ―western‖, ―traditional‖ and ―mixed‖. ―Western‖ and ―mixed‖ diet patterns were associated with 35 g/week (p=0.021) and 24 g/week (p=0.041) higher GWG in normal weight and obese women respectively. High intakes of the ―traditional‖ diet pattern were associated with a reduced odds of excessive weight gain in the total sample (OR: 0.81; p=0.006) and in normal weight women (OR: 0.68; p=0.003). In the final, fully adjusted study models, maternal obesity and GWG were associated with 0.25 kg/m (P=0.008) and 0.48 kg/m (P=0.002) higher newborn WLR, while ―traditional‖ diet pattern score was associated with lower newborn WLR (-0.04 per +1 SD; P=0.033). Additionally, ―traditional‖ pattern score was associated with 0.13 kg/m3 (P=0.027) and 0.32 kg/m3 (P=0.005) lower FMI in the total sample and in newborns of normal weight women, respectively. HIV positive (pre-pregnancy ART) vs. HIV negative (ref) status was associated with 1.11 kg/m3 (P=0.002) higher newborn FMI in a fully adjusted model. Conclusion: This thesis confirms the rapid transition in MNS across urban African populations and demonstrates the implications that the rise in maternal overweight and obesity alongside poor dietary patterns and micronutrient deficiencies may have on birth outcomes, as well as potentially on longer term health trajectories. However, it also highlights a lack of data on infant outcomes beyond birth, and therefore, a need for longitudinal data that examines longer-term implications in the African setting. In South Africa in particular, the thesis indicates that promotion of a traditional-style diet pattern - high in whole grains, legumes, vegetables and traditional meats and low in processed foods - alongside a healthy preconception weight in urban, black women would significantly improve both maternal and infant adiposity profiles. This may have substantial benefits in reducing long-term risk of non-communicable diseases in both current and future generations. However, the need for a holistic approach which incorporates other health and lifestyle determinants of growth and adiposity in the infant is critical in optimising metabolic health trajectories. In HIV-positive women for example, development of targeted monitoring and management strategies is necessary in order to limit the treatment-specific effects on adiposity in the newborn.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in the fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa 2018.
Keywords: Maternal Nutritional Physiological Phenomena; HIV; Infant, Newborn; Pregnancy; Maternal Welfare